Emerging ocular biomarkers of Alzheimer disease. (19th December 2016) - van Wijngaarden, Peter; Hadoux, Xavier; Alwan, Mostafa; Keel, Stuart; Dirani, Mohamed
Abstract: Interest in reliable biomarkers of Alzheimer disease, the leading cause of dementia, has been fuelled by challenges in diagnosing the disease and monitoring disease progression as well as the response to therapy. A range of ocular manifestations of Alzheimer disease, including retinal and lens amyloid‐beta accumulation, retinal nerve fiber layer loss, and retinal vascular changes, have been proposed as potential biomarkers of the disease. Herein, we examine the evidence regarding the potential value of these ocular biomarkers of Alzheimer disease.